2020
DOI: 10.1101/2020.09.07.20188813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking Smell Loss to Identify Healthcare Workers with SARS-CoV-2 Infection

Abstract: Background: Healthcare workers (HCW) treating COVID-19 patients are at high risk for infection and may also spread infection through their contact with vulnerable patients. Smell loss has been associated with SARS-CoV-2 infection, but it is unknown whether monitoring for smell loss can be used to identify asymptomatic infection among high risk individuals, like HCW. Methods: We performed a prospective cohort study, tracking 473 HCW across three months to determine if smell loss could predict SARS-CoV-2 infect… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…These results are in line with a Big Data analysis made in Spain, in which it was shown an age-dependent increase in reported cases in both males and females, being patients >79 yrs the most affected. [21] Regarding symptoms upon diagnosis, headache, anosmia, and taste distortion were significantly more frequent in women than men in the before mentioned analysis. In our population, there was less headache reported by older patients.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…These results are in line with a Big Data analysis made in Spain, in which it was shown an age-dependent increase in reported cases in both males and females, being patients >79 yrs the most affected. [21] Regarding symptoms upon diagnosis, headache, anosmia, and taste distortion were significantly more frequent in women than men in the before mentioned analysis. In our population, there was less headache reported by older patients.…”
Section: Discussionmentioning
confidence: 80%
“…[18,19] These differences could be explained because our population is mainly composed of HCP, mostly female, which could constitute a bias, and as it has been previously published, female affected of COVID-19 may be at higher risk to developing SD. [12,15,20,21] In a recent study published in Spain a total of 157/230 (68%) HCP described SD and 161/230 (70%) reported TD, with similar prevalence independently of age or sex. In contrast, in our sample females were significantly more affected than males in terms of STD, as it has been shown in a study using Big Data in Spain.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…More importantly, recent studies have now shown that olfactory loss is the best predictor of SARS-CoV-2 infection; indeed, it is potentially superior to other symptoms that the CDC and the World Health Organization (WHO) have determined to be relevant such as fever, cough, headache, and fatigue ( Gerkin et al, 2021 ). Not only is smell loss an early symptom of COVID-19 ( Klopfenstein et al, 2020 ; Levinson et al, 2020 ; Salje et al, 2020 ), olfactory dysfunction has been shown to precede positive polymerase chain reaction (PCR) findings by a median of 2 days ( Weiss et al, 2020 ). Given that to date over 185 million people worldwide have been infected with SARS-CoV-2, daily assessment of olfactory function has enormous public health potential.…”
Section: Case 1 Clock Regulation At the Point Of Infection: Altered Olfaction In Covid-19 Patientsmentioning
confidence: 99%
“…Beyond smell loss per se, Weiss et al (2020) found that parosmia—qualitatively altered olfactory perception where an odor is detected but is perceived unusually and typically as unpleasant—was the first symptom reported in a third of the positive cases where smell dysfunction occurred. Germane to the neurological significance of olfaction in COVID-19, the same study found that all COVID-19 positive individuals who indicated olfactory dysfunction also self-reported neurological symptoms such as headache, dizziness, or fatigue; a small subset of whom experienced prolonged neurological symptoms (≥ 20 days after receiving a positive test).…”
Section: Case 1 Clock Regulation At the Point Of Infection: Altered Olfaction In Covid-19 Patientsmentioning
confidence: 99%